THE AESTHETICS AND REVIVAL OF MODERN UZBEK FICTIONAL NARRATIVES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
In world literary studies, since the mid-20th century, the novella (short novel) genre, which followed the novel in prominence, has increasingly focused on the in-depth analysis of reality and the human psyche, as well as on conveying the essence of life. The structure, characters, conflicts, psychological depth, artistic and figurative devices, and the wide thematic scope of works created in this genre define the principles of its renewal. Naturally, understanding the current literary process, adopting an appropriate approach to artistic works, and comprehending the poetics of the novella genre in prose have created the need for distinctive theoretical knowledge and analytical skills in literary scholarship.